Family practices during the pandemic and the state of emergency – the female perspective - Čikić, Jovana M; Bilinović Rajačić, Ana (Sociološki pregled, 2020)
Increased risks are inspiring context for family practices’ analysis as they can impact changes in practices, thus changing family functioning and relations. The aim of the paper is to identify features of the main family practices (reproduction of everyday life, partnership, parenthood) during pandemic and state of emergency in Serbian society. It is assumed that these conditions led to practices’ changes. The issue is analysed based on data collected on a sample of 265 female respondents using a combined research plan. The results showed that the state of emergency and the pandemic of COVID-19 virus induced changes in main family practices. The most common were changes in the reproduction of everyday life (especially, groceries shopping), while pre-pandemic partnership practices were the most resistant to change. Traditional and egalitarian practices showed greater resilience to change, while masculine practices are usually newly established. There is continuity in the use of “female” resources in family practices, but with a shift from this pattern towards more frequent engagement of “male” resources, due to changes in the professional roles during the state of emergency.
Keywords: family practices; state of emergency; COVID-19 pandemic